2009
DOI: 10.1310/tsr1602-105
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Caregiver Outcomes from the Telephone Assessment and Skill-Building Kit (TASK)

Abstract: Purpose Stroke caregivers often express the need for information about stroke and assistance with stroke-related care in the early discharge period. The Telephone Assessment and Skill-Building Kit (TASK) is an 8-week program that addresses caregiver needs. This study explored the efficacy of the TASK program in improving stroke caregiver outcomes. Method Guided by a conceptual model, 6 outcomes (optimism, task difficulty, threat appraisal, depressive symptoms, life changes, general health perceptions) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
186
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(198 citation statements)
references
References 72 publications
4
186
1
7
Order By: Relevance
“…30 Fifteen of the studies involved a dyad intervention in which survivors were enrolled. Nine of the studies had samples sizes <50 caregivers, 27,35,42,44,50,52,55,58,60,62 although much can be learned from these small studies. Some reported effect sizes for a larger trial, 50,60 and others reported positive caregiver outcomes such as reduced depressive symptoms, 44,55 improved problem solving and preparedness, 44 and improved knowledge and satisfaction.…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Fifteen of the studies involved a dyad intervention in which survivors were enrolled. Nine of the studies had samples sizes <50 caregivers, 27,35,42,44,50,52,55,58,60,62 although much can be learned from these small studies. Some reported effect sizes for a larger trial, 50,60 and others reported positive caregiver outcomes such as reduced depressive symptoms, 44,55 improved problem solving and preparedness, 44 and improved knowledge and satisfaction.…”
Section: Samplesmentioning
confidence: 99%
“…Future studies should be responsive and tailored to both the needs of the care of the survivor and the unique needs of the family caregiver. 25,27,38,40,41,[44][45][46][47][48][49][50][51][52][53][54][55][56][58][59][60][61] 17 (53.1) 4 (23.5) 16 (94) Stroke survivor-caregiver dyad 26,[28][29][30][31][32][33][35][36][37]39,42,43,57,62,63 15 ( Psycho-educational 26,29,33,37,39,42,58 7 (21.9) 6 (85.7) 6 (85.7)Skill building and psycho-educational 25,27,28...…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies examining the effects of educational interventions on quality of life or functional status in elderly people show response rates of 30.9% [5], 59.6% [6], 62.6% [7], 77.1% [8], or 99.6% [9]. However in some studies it is not comprehensible why the authors differentiate between eligible patients and patients fulfilling inclusion criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the sample sizes are not clear. If the authors reported reasons for nonparticipation these were refusal or decline to participate [5,6,7] or lack of consent [8].…”
Section: Introductionmentioning
confidence: 99%